Skipping sex: A nonrecombinant genomic assemblage of complementary reproductive modules. (9th November 2020) - Hojsgaard, Diego; Schartl, Manfred
Abstract: The unusual occurrence and developmental diversity of asexual eukaryotes remain a puzzle. De novo formation of a functioning asexual genome requires a unique assembly of sets of genes or gene states to disrupt cellular mechanisms of meiosis and gametogenesis, and to affect discrete components of sexuality and produce clonal or hemiclonal offspring. We highlight two usually overlooked but essential conditions to understand the molecular nature of clonal organisms, that is, a nonrecombinant genomic assemblage retaining modifiers of the sexual program, and a complementation between altered reproductive components. These subtle conditions are the basis for physiologically viable and genetically balanced transitions between generations. Genomic and developmental evidence from asexual animals and plants indicates the lack of complementation of molecular changes in the sexual reproductive program is likely the main cause of asexuals' rarity, and can provide an explanatory frame for the developmental diversity and lability of developmental patterns in some asexuals as well as for the discordant time to extinction estimations. Abstract : Asexuality arises through developmental alterations with apparently unrelated origins. We show the occurrence of asexual animals and plants have a common genetic and developmental basis on a single nonrecombinant assemblage of genomic elements altering complementary reproductive modules. This explains asexuals' developmental diversity and biologically vague cases like automixis and polyploidy.